2016
DOI: 10.1037/ocp0000023
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing well-being at work: The role of emotion regulation skills as personal resources.

Abstract: Dealing with negative emotions is a crucial work demand, particularly for employees in health care. Job resources (e.g., autonomy, social support, or reward) but also personal resources (such as emotion regulation strategies) might reduce job stress and support well-being. Following this, the present study focused on strengthening emotion regulation as 1 way of dealing with high job demands. The aim of this study was to evaluate the impact of a standardized emotion regulation training (Affect Regulation Traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(118 citation statements)
references
References 86 publications
3
102
0
5
Order By: Relevance
“…Training programs may be one way to encourage healthy processing of emotion. For example, Buruck, Dörfel, Kugler, and Brom () demonstrated that a standardized emotion regulation training (Affect Regulation Training) improved employees' emotion regulation skills and well‐being. Thus, providing similar trainings to employees might help them effectively regulate their anger driven by experiences of illegitimate tasks and thus potentially reduce the occurrence of CWB as a result of illegitimate tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Training programs may be one way to encourage healthy processing of emotion. For example, Buruck, Dörfel, Kugler, and Brom () demonstrated that a standardized emotion regulation training (Affect Regulation Training) improved employees' emotion regulation skills and well‐being. Thus, providing similar trainings to employees might help them effectively regulate their anger driven by experiences of illegitimate tasks and thus potentially reduce the occurrence of CWB as a result of illegitimate tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Successful regulation of negative affect is crucial for mental health and well-being [1, 2]. Deficient emotion regulation (ER) and exaggerated anxiety represent transdiagnostic markers across major psychiatric disorders, including the most prevalent axis I disorders such as anxiety and addiction as well as axis II disorders [3-5; see also recent meta-analysis in 6].…”
Section: Introductionmentioning
confidence: 99%
“…social exchange perspective) and employees' knowledge and skills (i.e. human capital approach), but also requires employees' personal resources, especially when encountering sustained stress or challenge (Buruck et al 2016). Personal resources are positive self-evaluations that are linked to resiliency, and refer to individuals' sense of ability to control and influence their environment successfully (Xanthopoulou et al 2009).…”
mentioning
confidence: 99%